EFECTIVITY MINOXIDIL AS A TREATMENT OF ALOPECIA AREATA - Wayan Evie Frida Yustin (E-Jurnal Medika Udayana, 2014)
Alopecia areata is hair loss with patchy formation, the most common cause of alopecia nonscarring. Occurred in 1,7 % of Americans aged 50 years. Canoccurs in both sexes, all races and any age. Genetic and immunological factorsplay an important role as a cause of Alopecia areata. The clinical features alopecia areata are round or oval lesions, total baldness, smoothness on the scalpor other parts of the body that has hair. Minoxidil is one of the effective therapyfor Alopecia areata. Known for more than 30 years of minoxidil to stimulate hairgrowth. Minoxidil works on hair follicles, opening the potassium channels, andhave vascular effects that can increase blood flow to hair. Histological studiesshowed that minoxidil therapy may increase the proportion hair follicles in anagenphase and decrease hair follicles at telogen phase. Minoxidil through sulphatmetabolites can open potassium channels, the opening potassium channels canincrease the hair follicles growth. The study of the effects minoxidil on humanepidermal keratinocytes and hair follicles with different culture conditions andmarkers proliferation, found that minoxidil with micro molar concentration canstimulate proliferation both type of cells and all culture condition, whereasminoxidil with milimolar concentration will inhibit cell growth. In addition,several studies have also reported an association minoxidil to vascular effect andstimulating VEGF can promote the increase hair follicle